Mediation Model of Digital Technology Factors Affecting Health Care Service Performance - Abdulla Alzaabi, Hassah Obaid Ebrahiem; Hasan, Hazmilah; Akmal, Suriati (International Journal of Sustainable Construction Engineering and Technology, 2022)
Healthcare technologies have become a crucial component of healthcare providers' daily operations. Hence, healthcare innovation technologies are being promoted worldwide. Healthcare service technologies are constantly improving necessitates ongoing research to show how these technologies affect healthcare services. Hence, current study investigating the state of innovative digital healthcare service practises in the UAE. It examining the effect of innovative technology on healthcare service performance in the UAE and modeling mediating role of organisational learning capacity in the relationship between innovative technology and healthcare service performance. A structural equation model was developed in SmartPLS software using the data collected of the questionnaire. The model showed that the factors system development, digital services, process integration, and IT base innovations have strong relationship effect to the health care performance. Also, the organisational learning capacity has strong mediation effect on the health services relationship. This research has contributed to current state of literatur regarding digital service innovations related to health service performance in the UAE. The results exphasized a critical need for practationners for promoting developments in digital services impacted the performance of health services.